Comparative Performance Analysis of Banking For Implementing Internet Banking - Reza Kurniawan; Sarjito Surya (Bandar Lampung University (UBL), 2013)
Internet Banking is the application of information technology in the world of network-based digital perbankan. In i-banking businesses, customers are given the convenience of doing a variety of activities offered by the banking transactions via access of internet. For banks, i-banking is a strategy to compete. Expected to achieve efficiency and effectiveness by cutting marketing and distribution channels and a variety of financing. With the efficiency and effectiveness is achieved it will affect the performance of the bank itself. The purpose of the research object seven banks, namely Bank International Indonesia Tbk. (BII), Bank Central Asia Tbk. (BCA), Bank Lippo Tbk., Bank Niaga Tbk., Bank Permata Tbk., Bank Danamon Tbk., Bank Mandiri Tbk. is to determine the extent of the significance of financial performance on the seven banks before and after application of i-Banking. This study uses a case study approach to the comparative method Hypothesis testing is done with t-test.Data used are secondary data from financial statements of the Securities Exchange Jakarta.Kemudian of one variable with another variable than whether there are differences between the financial performance of banks at the time before and after application of i-Banking.Dalam measuring the financial performance, use two indicators, namely return on assets (ROA) and Return on Equity (ROE).